2019
DOI: 10.1103/physrevd.100.083529
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of dark matter microhalos through stellar encounters

Abstract: In the cold dark matter scenario, the smallest dark matter halos may be earth-mass or smaller. These microhalos would be the densest dark matter objects in the Universe, making their accurate characterization important for astrophysical dark matter detection efforts. Moreover, their properties are closely linked to the nature of dark matter and the physics of the early Universe, making them valuable cosmological probes. Dark matter microhalos survive as subhalos within larger galactic halos, but due to their s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 111 publications
1
42
0
Order By: Relevance
“…We also note that our model may not capture decreased central density due to heating, though we suspect that neglecting this is valid, as it has been found that the central regions of haloes are adiabatically shielded from heating (Weinberg 1994a,b). However, as shown in Delos (2019b), including the effects of stellar encounters on the subhalo can cause heating of all particles in the subhalo, resulting in a change in the DF. Incorporating the effects of these more complicated merging scenarios is a potential extension to our model.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that our model may not capture decreased central density due to heating, though we suspect that neglecting this is valid, as it has been found that the central regions of haloes are adiabatically shielded from heating (Weinberg 1994a,b). However, as shown in Delos (2019b), including the effects of stellar encounters on the subhalo can cause heating of all particles in the subhalo, resulting in a change in the DF. Incorporating the effects of these more complicated merging scenarios is a potential extension to our model.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most neutralino simulations find that the initial internal structure of microhalos is better described by a single power law profile $ r À1:5 , as first pointed out by Diemand et al (2005) (see also Ishiyama et al 2009;Anderhalden and Diemand 2013;Ishiyama 2014;Ogiya et al 2016;Angulo et al 2017;Delos et al 2019). This very steep profile would make microhalos very resilient to tidal disruption by the Milky Way or by binary stars and also would enhance their corresponding emission from dark matter self annihilation, making them potentially detectable by future experiments (Diemand et al 2006;Ishiyama et al 2009;Ishiyama 2014;Delos 2019), although their abundance is affected by free streaming (Ishiyama and Ando 2020). This power-law profile, however, quickly mutates to a NFW-like profile for higher mass halos.…”
Section: Weakly-interacting Massive Particlesmentioning
confidence: 94%
“…Refs. [848,849] and star clusters [850,851,852] and later in the context of microhalos themselves [853,854,855,856]. Ref.…”
Section: The Microhalo Population Within Galaxiesmentioning
confidence: 99%
“…Due to the relative rarity of stars, the impact of stellar encounters is highly stochastic, with the few closest encounters dominating a microhalo's evolution [824]. Additionally, unlike tidal evolution, a penetrative encounter can disrupt a microhalo's divergent central density cusp [856], potentially leading to its destruction.…”
Section: The Microhalo Population Within Galaxiesmentioning
confidence: 99%